Effects of rumination and mindful self-focus inductions during daily life in patients with remitted depression: an experimental ambulatory assessment study - Kühner, Christine; Schricker, Isabelle; Nayman, Sibel; Reinhard, Iris; Zamoscik, Vera; Kirsch, Peter; Huffziger, Silke (Behavior therapy, 2023)
Rumination has been proposed as an important risk factor for depression, whereas mindful attention is considered a protective form of self-focusing. Experimental studies have demonstrated differential effects of these modes when induced in the lab. However, their impact on daily life processes is poorly understood, particularly in individuals vulnerable to depressive relapses. The aim of our study was to examine short- and longer-term effects of repeated brief rumination and mindful self-focus inductions during daily life on momentary mood, cognitions, and cortisol in patients with remitted depression (rMDD) as well as in healthy individuals, and to identify their potential differential effects in these groups. The study involved repeated short ambulatory inductions of a ruminative or a mindful self-focus during daily life with additional assessments of momentary mood, rumination, self-acceptance, and cortisol over 4 consecutive days in a sample of patients with rMDD (n=32, ≥2 lifetime episodes, age 19-55 years) and matched healthy controls (n=32, age 21-54 years). Multilevel models revealed differential immediate effects of the two induction modes on all momentary mood and cognitive outcomes (all p’s<.001), but not on cortisol. Detrimental effects of rumination over mindful self-focus inductions were particularly strong for cognitions in the patient group. Longer-term effects of the inductions over the day were lacking. This study underlines immediate deteriorating effects of an induced ruminative compared to a mindful self-focus on momentary mood and cognitions during daily life in patients with rMDD and in healthy individuals. The observed stronger rumination-related reactivity in patients suggests heightened cognitive vulnerability. Understanding rumination- and mindfulness-based mechanisms of action in real-life settings can help to establish mechanism-based treatment options for relapse prevention in depression.
Online verfügbar: 8. Mai 2023, Artikelversion: 17. August 2023
Gesehen am 16.10.2023